2023
DOI: 10.1002/adma.202307705
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa‐Inspired Electro‐Responsive Lubricating Supramolecular‐Covalent Hydrogel

Jianye Kang,
Xuewei Zhang,
Xinyu Yang
et al.

Abstract: Enabling the living capability of secreting liquids dynamically triggered by external stimuli while maintaining the bulk frame is a significant challenge for mucosa‐inspired hydrogels. A mucosa‐inspired electro‐responsive hydrogel is developed in this study using the synergy between electro‐responsive silk supramolecular non‐covalent networks and covalent polyacrylamide and polyvinyl alcohol polymer networks. The formed supramolecular‐covalent hydrogel exhibits a partial gel‐sol transition upon the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Wenlong Song’s group developed a mucosa-inspired electro-responsive hydrogel consisting of an electro-responsive supramolecular noncovalent section (silk fibroin) and a covalent polymer interpenetrating network (polyacrylamide/polyvinyl alcohol double network (PAAm/PVA)) [ 40 ]. When an electric field is applied to the supramolecular hydrogel, it generates a partial gel-sol transition due to the disassembly of the silk fibroin network ( Figure 14 a).…”
Section: Supramolecular Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Wenlong Song’s group developed a mucosa-inspired electro-responsive hydrogel consisting of an electro-responsive supramolecular noncovalent section (silk fibroin) and a covalent polymer interpenetrating network (polyacrylamide/polyvinyl alcohol double network (PAAm/PVA)) [ 40 ]. When an electric field is applied to the supramolecular hydrogel, it generates a partial gel-sol transition due to the disassembly of the silk fibroin network ( Figure 14 a).…”
Section: Supramolecular Assemblymentioning
confidence: 99%
“… ( a ) The schematic diagram of the electro-responsive mechanism of the mucosa-inspired hydrogel under an electric field [ 40 ]. ( b ) The molecular structural formulas of the components of the hydration lubrication surface.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the concentrated acid will lead to the degradation of SF; HFIP is expensive, corrosive, and toxic; the highly concentrated inorganic salt solutions require long-time dialysis treatment and exhibit poor solution stability, and the dissolution process will also lead to the degradation of SF . Recently, ionic liquids (ILs) are widely acknowledged as green solvents due to their excellent chemical stability, thermal stability, nonflammability, and recyclability, and some kinds of ILs have exhibited great potential for biopolymer dissolution and processing, including cellulose, chitin, chitosan, and SF. , The first study of SF dissolution in ILs was conducted in 2004 by Phillips et al, and the results showed that the solubility of SF was highly correlated to the IL structure, which has stimulated much effort into preparing regenerated SF-based materials, such as fibers, films, hydrogels and scaffolds, demonstrating a feasible way for the value-added SF resources . Indeed, the use of ILs for SF processing and conversion, even other natural polymers, resented significant advantages over traditional solvent systems from not only a green technology but material properties point of view. , ILs are typically classified as protic ILs and aprotic ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Host–guest supramolecular hydrogels responding to environmental stimuli such as light, 1 temperature, 2 redox agents 3 and pH 4 have the potential to be used in controlled drug release, 5,6 artificial muscles and actuators, 7,8 self-healing, 9,10 shape-memory materials, 11,12 etc. To the best of our knowledge, supramolecular hydrogels that respond to three or more stimuli simultaneously are of great importance because they can generate more flexibility for complex environmental stimuli and have a wider range of applications with the coordination of different stimuli.…”
Section: Introductionmentioning
confidence: 99%